DETERMINAN TINGKAT PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN DI BEI - Singgih, Marmono; Farida, Lilik; Iwanda, Risqi Akbar (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract: The Corporate social responsibility (CSR) is a program designed to balance the company’s economic profits and its contribution to the economy, social, community, and environment. Food and beverage companies have a high production level that produces waste harmful of the people's lives. Public needs the information to what extent the company runs its CSR activities so the people’s right to live safely and healthily, the employee welfare, and the product safety is met. If the community perceives that the company neglects the social and environmental aspects, has no contribution to the community, and even causes a negative impact, it will lead to community resistance. Therefore, the disclosure of a company’s CSR activities is crucial. The research population was all manufacturing companies in food and beverages sub-sector listed on the Indonesia Stock Exchange in 2012-2015. There were 14 companies registered in 2012-2015 with the number of observations consisted of 56 companies’ annual reports. The sample was taken using purposive sampling method. Results show that profitability, company size, and public ownership have a significant effect on the level of CSR disclosure, while leverage and commissioners have no significant effect on the level of CSR disclosure. Keywords: CSR, Level of CSR Disclosure.